ERS statement on paediatric long-term noninvasive respiratory support. - Fauroux, Brigitte; Abel, Francois; Amaddeo, Alessandro; Bignamini, Elisabetta; Chan, Elaine; Corel, Linda; Cutrera, Renato; Ersu, Refika; Installe, Sophie; Khirani, Sonia; Krivec, Uros; Narayan, Omendra; et al. (European Respiratory Review, 2022)
Long-term noninvasive respiratory support, comprising continuous positive airway pressure (CPAP) and noninvasive ventilation (NIV), in children is expanding worldwide, with increasing complexities of children being considered for this type of ventilator support and expanding indications such as palliative care. There have been improvements in equipment and interfaces. Despite growing experience, there are still gaps in a significant number of areas: there is a lack of validated criteria for CPAP/NIV initiation, optimal follow-up and monitoring; weaning and long-term benefits have not been evaluated. Therapeutic education of the caregivers and the patient is of paramount importance, as well as continuous support and assistance, in order to achieve optimal adherence. The preservation or improvement of the quality of life of the patient and caregivers should be a concern for all children treated with long-term CPAP/NIV. As NIV is a highly specialised treatment, patients are usually managed by an experienced paediatric multidisciplinary team. This statement written by experts in the field of paediatric long-term CPAP/NIV aims to emphasise the most recent scientific input and should open up new perspectives and research areas.